The Effect of Oral Adenosine Triphosphate (ATP) Supplementation on Anaerobic Exercise in Healthy Resistance-Trained Individuals: A Systematic Review and Meta-Analysis - Roberto González-Marenco; Ivonne Azeret Estrada-Sánchez; Martha Medina-Escobedo; Rodolfo Chim-Aké; Roberto Lugo (MDPI AG, 2024)
Adenosine triphosphate (ATP) is an energy and signaling molecule. It is synthesized endogenously and can be taken as an oral supplement. This review aimed to identify the effects of oral ATP supplementation on anaerobic exercise in healthy resistance-trained adults. A systematic review and meta-analysis were performed based on the Preferred Reporting Items of Systematic Reviews and Meta-Analysis (PRISMA) criteria. The inclusion criteria were articles published from 2000 to 2022, with anaerobic variables (maximal strength, maximum repetitions, and maximum anaerobic power) measurable in healthy adults with experience in resistance training, only randomized placebo-controlled clinical trials (RCTs), and with the acute (a single dose 30 min to 24 h before the tests) and/or chronic (>1 day) oral supplementation of ATP. A total of five RCTs with 121 adult men were included. The oral ATP supplementation achieved significantly greater gains in maximal strength compared with the placebo (PL) (MD = 8.13 kg, 95%CI [3.36-12.90], p < 0.001). Still, no differences were observed in the maximum number of repetitions or the maximum anaerobic power. Furthermore, 400 mg of ATP showed improvement in anaerobic exercise regardless of the duration of the supplementation protocol. In conclusion, supplementation with 400 mg of ATP doses can improve maximal muscle strength in resistance-trained men.